KUAT TEKAN BETON DENGAN VARIASI CAMPURAN AGREGAT DAN SIKAGROUT 215 - A.Rudi Hermawan; EKA SASMITA MULYA (Jurnal Poli-Teknologi, 2014)
Recently, product elemen of precast have known many people in Indonesia. Point stresses of product precast is a joint elements of precast. The question is how to minimize costing of grouting elements precast. In this paper have tested mixing grouting materials product sika grout 215 with coarse aggregate This research have tested about mixing for grouting materials product sika grout 215 with coarse aggregate. That materials have tested with procentage of coarse aggregate 50%,40% and 30% of weigth of sika grout 215. Result of compression stresses for procentage of coarse aggregate 50%,40% and 30% of weigth of sika grout 215 is: (1) prosentage 50% of coarse aggregate result average compressive strength 329,5 kg/cm2 for 7 days, (2) prosentage 40% of coarse aggregate result average compressive strength 372,8 kg/cm2 for 7 days, (3) prosentage 30% of coarse aggregate result average compressive strength 376,7 kg/cm2 for 7 days, (4) prosentage 50% of coarse aggregate result average compressive strength 359,7 kg/cm2 for 28 days, (5) prosentage 40% of coarse aggregate result average compressive strength 408,2 kg/cm2 for 28 days, (6) prosentage 30% of coarse aggregate result average compressive strength 482,2 kg/cm2 for 28 days. Keynote : precast bolt joint,,wet connection